Protocol for conducting advanced cyclic tests in lithium-ion batteries to estimate capacity fade - Sai Krishna Mulpuri; Bikash Sah; Praveen Kumar (STAR Protocols, 2024)
Summary: Using advanced cyclic testing techniques improves accuracy in estimating capacity fade and incorporates real-world scenarios in battery cycle aging assessment. Here, we present a protocol for conducting cyclic tests in lithium-ion batteries to estimate capacity fade. We describe steps for implementing strategies for accounting for variations in rest periods, charge-discharge rates, and temperatures. We also detail procedures for validating tests experimentally within a climate-controlled chamber and for developing an empirical model to estimate capacity fading under various testing objectives.For complete details on the use and execution of this protocol, please refer to Mulpuri et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.